FORAMINIFERAL EVIDENCE FOR THE AGE OF EXOTIC BLOCKS WITHIN THE KOPRÍA MÉLANGE, RHODOS (GREECE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2005)
Blocks embedded within the Kopría Mélange of western Rhodos yield well-preserved, abundant microfossils including early Middle Pennsylvanian fusulinacean faunas represented by species belonging to the genera Eoschubertella, Profusulinella, Pseudostaffella and Ozawainella. A less diagnostic fauna mainly composed of the genus Paraachaediscus and an undetermined species of Howchinia has been also recorded and referred to a probable Mississippian age.This tropical to subtropical microfauna with Urals-Paleotethyan paleobiogeographic affinity provides new constraints for the paleogeographic interpretation of the Aegean region during the still poorly understood transition from the Variscan to the Alpine deformational cycle. In one olistolith, fusulinid-bearing strata are underlain by a basal conglomerate horizon whose composition indicates both "recycled orogenic" provenance and significant chemical weathering in a warm, humid climate. Sedimentologic and petrographic data, combined with the age and Urals-Paleotethyan affinity of the microfossil assemblages, are evidence for a major transgression that coincided in time with the end of the Variscan Orogeny. This may suggest original deposition of the mélange on the northern European margin of Paleotethys, although a southern origin be ruled out. Subsequent accretion to the External Hellenides, on the southern, Gondwanan margin of Paleotethys, could have taken place during the Eo-Cimmerian orogeny at the end of the Middle Triassic, shortly before the opening of the Pindos Basin.